Utiliser le tutorat par les pairs pour favoriser l’apprentissage de la lecture en milieu défavorisé. Une pré-expérimentation avec examen des caractéristiques des non-répondants - Potvin, Marie-Christine; Dion, Eric; Brodeur, Monique; Borri-Anadon, Corina (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
This pilot study examines the effectiveness of peer-mediated reading instruction in first grade classrooms. One class was assigned to the control condition, and three others to the intervention condition. Students who participated in the peer-mediated activities seem to have learned to pronounce letter sounds and to read words more quickly in comparison with their control counterparts, and also demonstrated better comprehension. Students who did not make progress were inattentive and had difficulties developing a good relationship with their teacher. Keywords: Pilot study, reading, peer-tutoring, non-responder.